Opportunities for changing teacher norms vary by underlying factors in teachers' selves, situations, standards, and society - Hwa, Yue-Yi (Frontiers in Education, 2024)
Teachers are pivotal to any attempts to raise the devastatingly low levels of foundational learning that persist across much of the Global South. However, in many education systems, teachers are not equipped with the resources for effecting such change. Moreover, numerous reform attempts have failed to change either children's learning levels or the teacher norms that inadvertently contribute to low learning levels. Moving beyond these circumstances requires an understanding of the factors underlying such norms, and how these factors affect opportunities for changing teacher norms. I examine this question by analyzing the transcripts of interviews with 14 pairs of interlocutors from various contexts, each of whom has complementary expertise related to teacher norms. Based on this analysis, I develop a conceptual framework for mapping the factors that sustain teacher norms across four domains of teachers' experiences: selves ("what I value"), situations ("what can be done"), standards ("what those in charge expect"), and society (broader influences). Different configurations of underlying factors can yield different types of norms: coherent norms, compromise norms, and contestation norms. Drawing on the interviews, I illustrate coherence, compromise, and contestation by discussing examples of teaching narrowly to certain standards and of being absent from the classroom during scheduled lessons. Each type of norm offers distinct opportunities for change by influencing particular aspects of teachers' selves, situations, and standards. Additionally, one broader opportunity for change is reshaping societal narratives about education and the teaching profession.